Synchronous Reality: Enhancing Sensory Perception in Immersive VR - Bailey, David Evans (Journal of Telecommunications and the Digital Economy, 2020)
This paper introduces the concept of Synchronous Reality whereby a combined sensory physical and virtual installation is created. The research is presented examining how the practice work evolved to establish the concepts which make up a Synchronous Reality installation. The research ultimately focused on creating a sensory landscape to complement the virtual layer of the installation, thus making a coherent whole which encompasses Synchronous Reality. The findings and conclusions indicate that this type of installation can increase the immersive quality and presence for the participant. The important considerations when making such an installation are also presented. The paper also touches upon a brief examination of the wider issues of how immersive virtual reality affects the digital economy and telecommunications.